Net-Zero Carbon Portfolio Alignment. Issue 2 (3rd April 2022) - Bolton, Patrick; Kacperczyk, Marcin; Samama, Frédéric
Abstract: We outline a simple and robust methodology to align portfolios with a science-based, carbon budget consistent with maintaining a temperature rise below 1.5 °C with 83% probability. We show how to keep the tracking error at a negligible level. This approach works for both passive and active managers. It also establishes an exit roadmap for carbon-intensive corporates, thereby generating a form of competition to decarbonize within each sector. We also discuss four sources of risks: uncertainty around a rapidly shrinking carbon budget, time impacts on decarbonization rates, implementation risk due to market-wide selling pressure, and uncertainty about taxes on polluting companies.